A Student-Run Asylum Clinic to Promote Human Rights Education and the Assessment and Care of Asylum Seekers - Nathan Praschan; Ranit Mishori; Nicholas Stukel (Journal of Student-Run Clinics, 2016)
Tens of thousands of individuals flee human rights violations in their home countries and seek asylum in the United States every year. Less than 40% receive protective status, leaving many torture victims rejected. However, 90% of asylees receiving a medical-legal affidavit are granted asylum, although demand for medical evaluations far exceeds the supply of trained clinicians. By establishing asylum clinics at their medical centers, medical students and licensed clinicians can improve the probability of an asylee obtaining asylum, connect them to vital services, and train more clinicians in their area to address the demand for evaluations. Asylum clinics are also unique educational opportunities for students interested in global health, social justice, and human rights. They operate by pairing student volunteers with clinician volunteers to meet with an asylum seeker for an evaluation. The evaluation involves extensive history-taking, a psychological exam, and a physical exam to note consistency between objective findings and the client’s story. The volunteer team then drafts a medical-legal affidavit for use by the client’s lawyer in immigration court. There may also be post-evaluation follow-up and connection with healthcare or other social services. Students at the Georgetown University School of Medicine (GUSoM) established an asylum program in 2014, hosted two training workshops, and have begun accepting clients’ requests for evaluations.  The GUSoM Asylum Program’s operations (including organizational structure and logistics of evaluation), educational opportunities (including mentorship and global health competency), and goals (including increasing capacity for evaluations and further developing partnerships with local stakeholders) are detailed below.